A randomized, controlled, double-blind crossover study on the effects of isoeffective and isovolumetric intravenous crystalloid and gelatin on blood volume, and renal and cardiac hemodynamics. Issue 7 (July 2020) - Bradley, Christopher R.; Bragg, Damian D.; Cox, Eleanor F.; El-Sharkawy, Ahmed M.; Buchanan, Charlotte E.; Chowdhury, Abeed H.; Macdonald, Ian A.; Francis, Susan T.; Lobo, Dileep N.
Summary: Background & aims: Blood volume expanding properties of colloids are superior to crystalloids. In addition to oncotic/osmotic properties, the electrolyte composition of infusions may have important effects on visceral perfusion, with infusions containing supraphysiological chloride causing hyperchloremic acidosis and decreased renal blood flow. In this non-inferiority study, a validated healthy human subject model was used to compare effects of colloid (4% succinylated gelatin) and crystalloid fluid regimens on blood volume, renal function, and cardiac output. Methods: Healthy male participants were given infusions over 60 min > 7 days apart in a randomized, crossover manner. Reference arm (A): 1.5 L of Sterofundin ISO, isoeffective arm (B): 0.5 L of 4% Gelaspan®, isovolumetric arm (C): 0.5 L of 4% Gelaspan® and 1 L of Sterofundin ISO (all B. Braun, Melsungen, Germany). Participants were studied over 240 min. Changes in blood volume were calculated from changes in weight and hematocrit. Renal volume, renal artery blood flow (RABF), renal cortex perfusion and diffusion, and cardiac index were measured with magnetic resonance imaging. Results: Ten of 12 males [mean (SE) age 23.9 (0.8) years] recruited, completed the study. Increase in body weight and extracellular fluid volume were significantly less after infusion B than infusions A and C, but changes in blood volume did not significantly differ between infusions. All infusions increased renal volume, with no significant differences between infusions. There was no significant difference in RABF across the infusion time course or between infusion types. Renal cortex perfusion decreased during the infusion (mean 18% decrease from baseline), with no significant difference between infusions. There was a trend for increased renal cortex diffusion (4.2% increase from baseline) for the crystalloid infusion. All infusions led to significant increases in cardiac index. Conclusions: A smaller volume of colloid (4% succinylated gelatin) was as effective as a larger volume of crystalloid at expanding blood volume, increasing cardiac output and changing renal function. Significantly less interstitial space expansion occurred with the colloid. Trial registration: The protocol was registered with the European Union Drug Regulating Authorities Clinical Trials Database (https://eudract.ema.europa.eu ) (EudraCT No. 2013-003260-32).